Cenozoic Cichlids of Africa (Cichlidae: Pseudocrenilabrinae) With the Description of a New Species From the Oligocene of Somalia - Murray, Alison M. (Frontiers in Earth Science, 2022)
Cichlid fishes are an important component of the African freshwater ecosystem and the evolution of this group has captured the interest of ichthyologists for many decades. The distribution of cichlid fishes in both Africa and South America, and the apparent reciprocal monophyly of the cichlids in the two areas, has led to differences in opinion as to whether their modern distribution reflects a dispersal event from Africa to South America or was the result of a vicariant event – the break-up of the two continental masses in the mid-Cretaceous. If the vicariant event were the cause of the modern distribution, this would indicate an age for the family of at least 120 million years; however, the fossil record indicates a younger, Cenozoic, age for the family. The known fossil taxa in Africa often are difficult to assign to extant tribes which creates inaccuracies when they are used to date lineages within Cichlidae. The difficulty of assigning fossil cichlids to modern lineages is caused by most of these lineages being recognized based on DNA or soft-tissue characters, which are generally not preserved in fossils. This hampers our understanding of the early history of the family. Despite this, new African cichlid fossils that have been described in the past two decades and a new technique to determine relationships of these fossils are beginning to elucidate the early history of the family in Africa. Here the Palaeogene (Eocene and Oligocene) cichlids of Africa are reviewed and a new taxon from the Oligocene of Somalia, Somalichromis hadrocephalus gen. et sp. nov. is described.